Isolation and comparison of tribe-specific centromeric repeats within Bovidae - Kopecna, Olga; Kubickova, Svatava; Cernohorska, Halina; Cabelova, Katerina; Vahala, Jiri; Rubes, Jiri (Journal of applied genetics, 2012)
A taxonomic division of the family Bovidae (Artiodactyla) is difficult and the evolutionary relationships among most bovid subfamilies remain uncertain. In this study, we isolated the cattle satellite I clone BTREP15 (1.715 satellite DNA family) and autosomal centromeric DNAs of members of ten bovid tribes. We wished to determine whether the analysis of fluorescence in situ hybridization patterns of the cattle satellite I clone (BTREP15) and tribe-specific centromeric repeats isolated by laser microdissection would help to reveal some of the ambiguities occurring in the systematic classification of the family Bovidae. The FISH study of the presence and distribution of the cattle satellite I clone BTREP15 (1.715 satellite DNA family) within members of ten bovid tribes was not informative. FISH analysis of autosomal centromeric DNA probes in several species within one tribe revealed similar hybridization patterns in autosomes confirming tribal homogeneity of these probes. Sex chromosomes showed considerable variation in sequence composition and arrangement not only between tribes but also between species of one tribe. According to our findings it seems that Oreotragus oreotragus developed its own specific satellite DNA which does not hybridize to any other bovid species analysed. Our results suggest O. oreotragus as well as Aepyceros melampus may be unique species not particularly closely related to any of the recognized bovid tribes. This study indicates the isolation of tribe-specific centromeric DNAs by laser microdissection and cloning the sequence representing the main motif of these repetitive DNAs could offer the perspectives for comparative phylogenetic studies.
Keywords: Cattle; laserová záchytná mikrodisekce; DNA Probes; Male; centromera; hybridizace in situ fluorescenční; fylogeneze; Centromere; skot; Phylogeny; biologická evoluce; mužské pohlaví; satelitní DNA; Animals; Ruminants; ženské pohlaví; Biological Evolution; DNA, Satellite; zvířata; Laser Capture Microdissection; DNA sondy; In Situ Hybridization, Fluorescence; Female; přežvýkavci